2015
DOI: 10.1002/pi.4930
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonium polyelectrolytes: influence of diphosphine spacer on layer‐by‐layer assembly with anionic conjugated polymers

Abstract: Three phosphonium polyelectrolytes have been prepared wherein the flexibility of the spacer between charge‐bearing phosphonium units was varied from 1,2‐ethyl to 1,4‐phenyl to 1,1′‐ferrocenyl. The influence of inter‐phosphonium spacer flexibility on the ability of the polyelectrolyte to form ordered films via layer‐by‐layer supramolecular assembly with anionic polythiophene and anionic poly(p‐phenylenevinylene) derivatives was also assessed through a combination of UV−visible spectroscopy and atomic force micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Compared with traditional organic frameworks, ionic hypercrosslinked polymers, specifically those involving ionic liquids as monomers, have attracted growing attention. These materials can possess good thermal and chemical stability, properties that can be tuned upon simple counterion exchange, and which can readily form layer‐by‐layer self‐assembled films with other ionic polymers . For example, Yang et al reported an alkaline anion exchange membrane R1 (Scheme ) comprised of copolymerized imidazolium‐functionalized ionic liquids with styrene and acrylonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional organic frameworks, ionic hypercrosslinked polymers, specifically those involving ionic liquids as monomers, have attracted growing attention. These materials can possess good thermal and chemical stability, properties that can be tuned upon simple counterion exchange, and which can readily form layer‐by‐layer self‐assembled films with other ionic polymers . For example, Yang et al reported an alkaline anion exchange membrane R1 (Scheme ) comprised of copolymerized imidazolium‐functionalized ionic liquids with styrene and acrylonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…Second, side chains are well‐known to lower the glass transition temperature and decrease crystallinity, and the interplay of these established trends with the influence of intercation spacer had not been examined for PELs. On the basis of prior studies on PELs, the improved solubility was also expected to lead to better film growth linearity for LbL self‐assembly films and smoother/more uniform films. Finally, the LO backbone is identical to that of the LX polymer series, allowing direct comparison of data for the two series in the effort to derive more general structure–property correlations.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular weights and degrees of polymerization are summarized in Table . Because these ionomers are too polar to efficiently pass through a gel permeation chromatography column, the degrees of polymerization were determined from NMR end‐group analysis . A slight excess of phosphine monomer was employed to ensure the identity of the end group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations